Teachers’ Preparedness for Effective Implementation of the Lower Secondary Competence-Based Curriculum in Rukungiri District, Southwestern Uganda - Gladyce Kachope; Viola N. Nyakato; Adrian Mwesigye (Journal of Research Innovation and Implications in Education, 2025)
The Competence-Based Curriculum (CBC) at Uganda's lower secondary school level depends significantly on teachers' preparedness. This study explored the relationship between teachers’ preparedness and the practical implementation of the CBC in Rukungiri District. Adopting a convergent parallel mixed methods design, the research engaged 235 in-service teachers through structured questionnaires and conducted key informant interviews with 13 head teachers. Quantitative data were analysed using descriptive statistics in Stata 17, while thematic analysis of qualitative data was conducted using NVivo 14. Findings revealed that while teachers reported high levels of perceived preparedness, particularly in classroom management, inclusivity, and learner-centred instruction, substantial gaps were evident in training adequacy, assessment practices, and ICT integration. Qualitative insights reinforced the importance of administrative support, peer collaboration, and resource provision as critical enablers of effective CBC delivery. The study underscores the need for continuous professional development and targeted resource allocation to bridge the preparedness gap. These findings contribute to curriculum implementation theory by affirming that teacher readiness, when holistically supported, is pivotal to transformative educational reform.
Keywords: Competence-Based Curriculum; Teacher Preparedness; Curriculum Implementation; Secondary Education; Mixed Methods; Uganda